Archive für Literatur Der Nachlass und seine Ordnungen - Dallinger, Petra-Maria; Hofer, Georg; Judex, Bernhard (Literatur und Archiv, 2018)
The series "Literature and Archive" establishes a common field of conversation between literary and edition science, archive theory, archival and cultural studies as well as the practice of today's archives.